Revisit Perito Implant® Technique : A Narrative Review - M M Afif; Nabil Dhiya Ulhaq (The International Journal of Medical Science and Health Research, 2025)
Infrapubic penile implant surgery is a viable option for patients with severe penile curvature, shortening, and        impaired penile rigidity due to fibrosis of the corpora cavernosa (Sadeghi-Nejad, 2007). Studies have shown that patients        who undergo penile implant surgery, particularly the infrapubic approach, experience significantly better erectile function and treatment satisfaction compared to those receiving other treatments such as sildenafil citrate and intracavernous prostaglandin E1 (Rajpurkar & Dhabuwala, 2003). The infrapubic approach offers advantages such as ease of reservoir placement, rapid implantation, and direct vision during the procedure, as well as avoiding an extra incision on the scrotum, which can hinder rehabilitation (Montague & Angermeier, 2000; Vollstedt et al., 2017). Additionally, it has     been noted that the infrapubic approach can be quickly learned by urologists who are already comfortable with the transscrotal approach (Kramer & Chason, 2010). However, it is important to consider the drawbacks associated with the infrapubic approach, such as the higher risk of surgical errors during the placement of the device in the corpora (Kramer et al., 2010)